Rivers of the Anthropocene (University of California Press, 2017)
This exciting volume presents the work and research of the Rivers of the Anthropocene Network, an international collaborative group of scientists, social scientists, humanists, artists, policymakers, and community organizers working to produce innovative transdisciplinary research on global freshwater systems. In an attempt to bridge disciplinary divides, the essays in this volume address the challenge in studying the intersection of biophysical and human sociocultural systems in the age of the Anthropocene, a new geological epoch of humans' own making. Featuring contributions from authors in a rich diversity of disciplines-from toxicology to archaeology to philosophy- this book is an excellent resource for students and scholars studying both freshwater systems and the Anthropocene.